2019
DOI: 10.1002/pssb.201800736
|View full text |Cite
|
Sign up to set email alerts
|

Auxetics and Other Systems of Anomalous Characteristics

Abstract: The present volume on materials and models with negative Poisson's ratio (which are often referred to as "auxetics") and other systems of anomalous characteristics is the thirteenth focus issue of physica status solidi (b) on this subject. [1] The volume contains twenty papers grouped into three sections: macroscopic auxetic materials and models, microscopic models of auxetics, and other systems of anomalous characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…It has also been found that novel properties, distinct from conventional or auxetic materials, arise when a composite structure is made from both conventional and auxetic materials. In addition to a recent comprehensive survey of auxetic materials and structures [ 37 ], the reader is also referred to a recent focus issue on “auxetics and other systems of anomalous characteristics” [ 38 , 39 , 40 , 41 , 42 ], as well as papers in this special issue [ 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that novel properties, distinct from conventional or auxetic materials, arise when a composite structure is made from both conventional and auxetic materials. In addition to a recent comprehensive survey of auxetic materials and structures [ 37 ], the reader is also referred to a recent focus issue on “auxetics and other systems of anomalous characteristics” [ 38 , 39 , 40 , 41 , 42 ], as well as papers in this special issue [ 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suffice to mention that 2019 marks the 15th anniversary of the first of the "Auxetics and Related Systems" international meeting held near Poznan Poland, an initiative of Professor Krzysztof Witold Wojciechowski, which has now become the most important annual gathering for scientists working in this field and has led to numerous specialized publications. [30][31][32][33][34][35][36][37][38][39][40][41][42] Systems which exhibit more than one unusual property (e.g., a combination of negative linear compressibility, negative thermal expansion, and/or negative Poisson's ratio), or ones which show a considerable change in at least one of their properties in response to an external stimulus, are becoming increasingly desirable in view of practical applications where they can be used. In fact, in recent years, there have been extensive studies aimed at developing such systems and to further improve their properties.…”
Section: Introductionmentioning
confidence: 99%
“…Materials science and mechanics have also witnessed a number of important developments, some of which are of a fundamental nature, such as the verification, through models and experiments, that materials need not get thinner when stretched . This has led to the coining of new terms to describe these new systems, such as “auxetic” (from the Greek word auxetikos , a term coined by Kenneth E. Evans, to describe systems which exhibit a negative Poisson's ratio), “metamaterials” or “mechanical metamaterials,” a testimony of the growth of this and related fields . Suffice to mention that 2019 marks the 15th anniversary of the first of the “Auxetics and Related Systems” international meeting held near Poznan Poland, an initiative of Professor Krzysztof Witold Wojciechowski, which has now become the most important annual gathering for scientists working in this field and has led to numerous specialized publications …”
Section: Introductionmentioning
confidence: 99%
“…Since its rediscovery in the late 1980s, [9][10][11][12][13] auxetic materials have been investigated for applications as cushions, [14,15] footwear, [16,17] aircraft structures, [18,19] shock and vibration control, [20][21][22][23][24][25] technical textiles, [26,27] chemical filters, [28][29][30][31] implants, [32][33][34][35][36][37] safety devices, [38] composite structures, [39,40] and even sport safety gear. [41,42] Further details of auxetic materials can be found in recent reviews by Saxena et al, [43] Lim, [44] Lakes, [45] and Ren et al [46] as well as recent special issues on auxetics in Physica Status Solidi B (e.g., previous studies [47][48][49] ), Materials (e.g., previous studies [50][51][52] ), and two monographs. [53,54] While auxeticity has often...…”
Section: Introductionmentioning
confidence: 99%